(untitled) (Fiep Bulletin - online, 2017)
The decrease in hospitalized patients is a worldwide reality and is one of the most frequent adverse events rangingfrom mild to more serious injuries, which can lead to death, and are responsible for the increase in patients’ morbidity, especiallyamong the elderly. In view of the dimension of the problem that falls within the hospital environment, this study had the objective ofanalyzing the falls of hospitalized adult patients, registered in the software of reports of adverse events of a University Hospital. Itis a quantitative, retrospective and descriptive study conducted at a University Hospital of Petrolina - PE. In the period fromJanuary to October 2016, 64 falls were identified in hospitalized patients, the percentage of patients who suffered falls was higherin males 83% (53) than in females 17% (11), the age of the patients ranged from 17 to 94 years, with a higher frequency in the agegroup between 36 and 50 years (29.6%), occurred in a higher percentage in the daytime period (56%), the largest proportion offalls occurred in the Emergency sector, 56% Prevalent in patients who were on stretchers and in the bed 56% at the time of theoccurrence. It is noticed that falls are incidental and continue to occur frequently in hospital settings. For this reason, this is areality that should be considered as a public health problem, which should be considered as a priority by the hospital’sgovernance to reach an increasingly lower incidence of this event.